2007
DOI: 10.1128/jcm.01871-06
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Analysis of Invasive Streptococcus pneumoniae from Mali, Africa, by Semiautomated Repetitive-Element PCR and Pulsed-Field Gel Electrophoresis

Abstract: Of the 12 serotypes present, the majority of isolates were not contained in PCV7 (the 7-valent pneumococcal conjugate vaccine), including 1 isolate that was serotype 1, 12 isolates that were serotype 2, 58 isolates that were serotype 5, 7 isolates that were serotype 7F, and 1 isolate that was serotype 12F. To determine whether clonal dissemination of the predominant serotypes had taken place, genotyping was performed on 100 S. pneumoniae isolates by using two methods: pulsed-field gel electrophoresis (PFGE) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
(50 reference statements)
2
19
0
1
Order By: Relevance
“…Comparable findings have been reported for Rep-PCR and PFGE for Acinetobacter baumannii, Streptococcus pneumoniae, and methicillin-resistant Staphylococcus aureus (MRSA) (9,17,18,21). Concordance and good reproducibility of Rep-PCR with PFGE for VRE was found in a laboratory-based study (16).…”
Section: Discussionsupporting
confidence: 54%
“…Comparable findings have been reported for Rep-PCR and PFGE for Acinetobacter baumannii, Streptococcus pneumoniae, and methicillin-resistant Staphylococcus aureus (MRSA) (9,17,18,21). Concordance and good reproducibility of Rep-PCR with PFGE for VRE was found in a laboratory-based study (16).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, our studies provide information on the applicability to S. pneumoniae of two typing methods, Rep-PCR and MLST with ESI-MS. The Barcodes Rep-PCR method has only been reported to have been used to type S. pneumoniae on one occasion, with PFGE used for comparison (14). In that study the investigators concluded that Rep-PCR was able to delineate S. pneumoniae with a discriminatory power equal to that of PFGE and suggested that it could be used as a stand-alone method for this species, with the only qualification that subtype groupings were more difficult to define by Rep-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from several colonies of an overnight subculture grown on blood agar plates and purified using an UltraClean microbial DNA isolation kit (MO BIO Laboratories, Carlsbad, CA). PCR amplification of 25 ng of purified DNA was performed with reagents provided in the DiversiLab DNA Enterococcus fingerprinting kit (bioMerieux, Hazelwood, MO) according to the manufacturer's instructions (the Enterococcus kit is recommended for S. pneumoniae) (14). PCR cycling conditions included an initial denaturation at 94°C for 2 min, followed by 35 cycles of 94°C for 30 s, 50 C for 30 s, and 70°C for 90 s, with a final extension at 70°C for 3 min.…”
Section: Typing By Pfgementioning
confidence: 99%
“…Genomic DNA was extracted in 1.6% InCert agarose plugs (Cambrex Corp., East Rutherford, NJ) following standard methods (17). DNA was digested with SmaI (New England Biolabs, Ipswich, MA) followed by PFGE performed using a CHEF DR III system (Bio-Rad Laboratories, Hercules, CA) as described previously (12). PFGE fingerprint profiles were interpreted according to the guidelines proposed by Tenover et al (25) and by the use of the program BioNumerics (Applied Maths, Belgium).…”
mentioning
confidence: 99%